THE ROLE OF FOREIGN LANGUAGES IN MODERN LIFE. - Xolmo’minova Nesbali Odiljon qizi; Axmedova Sevara Rakhmankulovna ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
English is used for more purposes. It is closely related to economic modernization, industrial development and today’s social life. Companies compete fiercely for customers while employees compete with each other for their jobs, Student's entry into a professional language environment certainly contributes to the intensification. The English language is rich in scientific and technical features. Foreign languages, especially many of these special words, are related to international words. In order to educate students' interest in the subject of "Foreign language" and to form them, the teacher should not interfere in the motivation field of students, but should learn to control it. The teacher should think about the problem of continuous formation. Motivation among students plays an important role as one of the main tasks of their activity.